PENGARUH PEMBERIAN WAFER RUMPUT GAJAH DENGAN PEREKAT FERMENTED MOTER LIQUOR (FML) DAN TETES (MOLASSES) TERHADAP KONSUMSI PAKAN, KECERNAAN ZAT-ZAT MAKANAN DAN KENAIKKAN BERAT BADAN SAPI BALI JANTAN: EFFECTS OF ADDITION OF FERMENTED MOTHER LIQUOR (FML) AND MOLLASES BINDERSIN ELEPHANT GRASS WAFER TOWA RDS FEED CON. UMPTION, NUTRIENT DIGESTIBILITY AND AVERAGE DAILY GAIN IN BULL - Lambertus E. Nuhuyanan (Fakultas Peternakan Universitas Papua, 2010)
The study conducted aimed to deeply know the effect of addition fermented mother liquor (FML) and mollases binder on elephant grass wafer towards feed consumption, nutrient digestibility and average daily gain (ADG) applied to the bull performances. Completed randomized design was experimentally applied as body weight was the covariance. Data analysis using Ancova was done to parameterise feed consumption, nutrient digestibility and average daily gain. The results shown that feed consumption and feed digestibility (DM, OM, BETN and CP) had shown strong significant declining effect (P<0.01) and feed digestibility had significantly increase (P<0.05) particularly in the components of CP and fat on voluntary feed intake (VFI) periods, and to increase the feed consumption dan feed digestibility had shown high significant (P<0.01) on feeding trials periods. There had no significant effect (P>0.05) on average daily gain and feed consumption as a result of treatments. In general, addition of FML and mollases ruled as solid (binder materials) in elephant grass-feeding based as wafer had shown no negative effect on feed consumption, nutrient digestibility and average daily gain. Wafer with mollases solid (binder) was better than other treatment.